OPTIMALISASI BIAYA DAN WAKTU PELAKSANAAN PROYEK PEMBANGUNAN PERUMAHAN CITRALAND PALU MENGGUNAKAN METODE PROGRAM EVALUATION AND REVIEW TECHNIQUE (PERT) – CRITICAL PATH METHOD (CPM) - Wardani, N M E; Musdalifah, S; Lusiyanti, D (Program Studi Matematika, Universitas Tadulako, 2018)
This study aimed to optimize the cost and time of implementation of development projects in residential homes Citraland located in the town of Palu subdistrict villages Mantikulore Tondo. Completion of construction of residential houses has been delayed time of completion of the construction. This leads to greater costs incurred in development projects. Therefore, to solve these problems is necessary to analyze the optimization of project time to determine how long a project is completed. Optimization of costs and project execution time is calculated using the Critical Path Method (CPM). The method is based on the results obtained, namely the normal completion time of the project for 69 weeks with a total cost of Rp. 297,887,212.00. Aftertime optimization through crashing eachthe implementation of the activities of the development to 48 weeks with a total cost of Rp. 350,261,175.00. The probability of completion of project design development using methods Program Evolution and Review Technique (PERT) is great opportunity to complete the project work for 48 weeks amounted to 93.19%